Ganglioside Alters Phospholipase Trafficking, Inhibits NF-κB Assembly, and Protects Tight Junction Integrity - Miklavcic, John J.; Li, Qun; Skolnick, Jordan; Thomson, Alan B. R.; Mazurak, Vera C.; Clandinin, Micheal Tom (Frontiers in Nutrition, 2021)
Background & Aims: Dietary gangliosides are present in human milk and consumed in low amounts from organ meats. Clinical and animal studies indicate that dietary gangliosides attenuate signaling processes that are a hallmark of inflammatory bowel disease (IBD). Gangliosides decrease proinflammatory markers, improve intestinal permeability, and reduce symptoms associated with IBD. The objective of this study was to examine mechanisms by which dietary gangliosides exert beneficial effects on intestinal health. Methods: Studies were conducted in vitro using CaCo-2 intestinal epithelial cells. Gangliosides were extracted from milk powder and incubated with differentiated CaCo-2 cells after exposure to proinflammatory stimuli. Gut barrier integrity was assessed by electron microscopy, epithelial barrier function was examined by measuring transepithelial electric resistance, and content of HBD-2, IL-23, NF-κB and secretory phospholipase A2 was assessed by ELISA. Results: Ganglioside attenuated the decrease in integrity of tight junctions induced by proinflammatory stimuli and improved epithelial barrier function (p<0.05). Ganglioside decreased the basolateral secretion of sPLA2 (P≤0.05), lowered HBD-2 and IL-23 levels (P≤0.05), and inhibited NF-κB activation (P≤0.05). Conclusions: In summary, the present study indicates that ganglioside GD3 improves intestinal integrity by altering sPLA2 trafficking, and the production of proinflammatory mediators is mitigated by decreasing assembly of the NF-κB complex. Dietary gangliosides have promising potential beneficial effects in IBD by decreasing inflammatory signaling, improving intestinal integrity, and maintaining epithelial barrier function